Pengembangan Bahan Ajar E-Modul Berbasis Geogebra Untuk Meningkatkan Kemampuan Berpikir Visual Siswa - Geo Wahyuni; Rita Destini; Abdul Mujib (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
This research was conducted with the aim of producing a valid, effective, and practical e-module teaching material product that can enhance students' visual thinking abilities. The research employed the Research and Development (R&D) research method, following the ADDIE stages. Data collection techniques included expert questionnaires on subject matter and media, teacher and student responses, as well as assessments conducted prior to (pretest) and after the learning process (posttest). The research was carried out on 36 students from the 11th grade of Sei Rampah State Vocational High School. The results of this study indicated that the validation by media experts was 82.50%, while subject matter experts provided a validation score of 81.00%. The student responses yielded a score of 91.82% for practicality and 81.17% for effectiveness. The teacher responses resulted in scores of 85.45% for practicality and 82.50% for effectiveness. Additionally, the average score of the pretest was 31.25, whereas the average score of the posttest was 80.28, with an N-Gain score of 70.09%. These findings demonstrate that the Geogebra-based e-module teaching material has a moderate impact on enhancing students' visual thinking abilities.